2013
DOI: 10.1590/s0100-40422013000100007
|View full text |Cite
|
Sign up to set email alerts
|

Stability-indicating comparative methods using mekc and lc for determination of olmesartan medoxomil

Abstract: Recebido em 24/2/12; aceito em 25/7/12; publicado na web em 11/12/12 A stability-indicating method using MEKC was validated for the analysis of olmesartan medoxomil in tablets. Successful separation was achieved using a fused silica capillary (40 cm x 50 μm i.d.); background electrolyte consisted of a combination of 10 mmol L -1 borate buffer and 5 mmol L -1 anionic detergent sodium dodecyl sulfate (95:5; v/v) pH 6.5; hydrodynamic mode at 50 mBar for 5 s; 25 kV separation voltage at 25 °C; and column temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A literature survey revealed that several analytical methods were reported for the determination of olmesartan medoxomil in pharmaceutical dosage forms and in biological fluids including liquid chromatography tandem mass spectrometry (LC-MS-MS), capillary electrophoresis (CE), UV spectrophotometry, LC and high performance thin layer chromatography (HPTLC) [7][8][9][10][11][12] . Olmesartan medoxomil determination has been reported for single preparations or in combination with other antihypertensive drugs [13][14][15][16][17][18] .…”
Section: Sensitive Liquid Chromatographic Assay For Simultaneous Dete...mentioning
confidence: 99%
“…A literature survey revealed that several analytical methods were reported for the determination of olmesartan medoxomil in pharmaceutical dosage forms and in biological fluids including liquid chromatography tandem mass spectrometry (LC-MS-MS), capillary electrophoresis (CE), UV spectrophotometry, LC and high performance thin layer chromatography (HPTLC) [7][8][9][10][11][12] . Olmesartan medoxomil determination has been reported for single preparations or in combination with other antihypertensive drugs [13][14][15][16][17][18] .…”
Section: Sensitive Liquid Chromatographic Assay For Simultaneous Dete...mentioning
confidence: 99%